2009
DOI: 10.1158/1535-7163.mct-09-0107
|View full text |Cite
|
Sign up to set email alerts
|

Xenogeneic immunization with human tyrosine hydroxylase DNA vaccines suppresses growth of established neuroblastoma

Abstract: Neuroblastoma (NB) is a challenging malignancy of the sympathetic nervous tissue characterized by a very poor prognosis. One important marker for NB is the expression of tyrosine hydroxylase (TH), the first-step enzyme of catecholamine biosynthesis. We could show stable and high TH gene expression in 67 NB samples independent of the clinical stage. Based on this observation, we addressed the question of whether xenogeneic TH DNA vaccination is effective in inducing an anti-NB immune response. For this purpose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Additionally, the immune response against H9 could lead to antigenic spread to induce protective immunity against NuTu-19 unique tumor antigens, a concept akin to what was proposed to explain the efficiency of xenogeneic antigen immunization. (Huebener et al, 2009) We have found cross-reactive proteins between H9 and NuTu-19 by Western-blot. The ability to separate and purify these proteins in order to find the exact antigen and to explore the antitumor mechanism of embryonic stem cells are both interesting questions worthy of further exploration.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, the immune response against H9 could lead to antigenic spread to induce protective immunity against NuTu-19 unique tumor antigens, a concept akin to what was proposed to explain the efficiency of xenogeneic antigen immunization. (Huebener et al, 2009) We have found cross-reactive proteins between H9 and NuTu-19 by Western-blot. The ability to separate and purify these proteins in order to find the exact antigen and to explore the antitumor mechanism of embryonic stem cells are both interesting questions worthy of further exploration.…”
Section: Discussionmentioning
confidence: 77%
“…Vaccination of mice with tyrosine hydroxylase DNA minigenes can induce CTLs, eradicate established primary NXS2 neuroblastoma tumors, and inhibit spontaneous metastases without induction of autoimmunity (29, 30). MYCN derived peptides have been reported to generate MHC class I restricted human CTL in vitro that lyse MYCN amplified human neuroblastoma cells (31).…”
Section: Cytotoxic T Lymphocytesmentioning
confidence: 99%
“…Another pre-clinical study have demonstrated that tyrosine hydroxylase and MYCN proteins, which are relatively specific for neuroblastoma cells compared to normal cells, include peptides that can be targets for CTL. Vaccination of mice with tyrosine hydroxylase DNA minigenes can induce CTLs, eradicate established primary NXS2 neuroblastoma tumors, and inhibit spontaneous metastases without induction of autoimmunity [84,85].…”
Section: Cd8mentioning
confidence: 99%